Molecular evidence of Enterocytozoon bieneusi in arid urban landscapes of shiraz cockroaches (Blattodea), Southwest Iran: Implications for urban public health surveillance - Mohsen Kalantari; Kourosh Azizi; Negin Kiani Junaghani; Mozaffar Vahedi; Iraj Mohammadpour; Qasem Asgari; Amin Hosseinpour; Mehdi Miri (Parasite Epidemiology and Control, 2025)
Microsporidia, particularly Enterocytozoon bieneusi and Encephalitozoon intestinalis, are emerging fungal pathogens of global concern, causing severe gastrointestinal and systemic infections in immunocompromised individuals. Cockroaches (Blattodea), as synanthropic pests, are potential mechanical vectors for disseminating these pathogens in urban environments. Despite their clinical significance, data on the role of cockroaches in transmitting microsporidia in arid regions remain scarce. This study assessed the contamination of cockroaches in Shiraz, Iran, with E. bieneusi and E. intestinalis to evaluate their public health risks. From January to June 2023, 378 cockroaches were collected from high-risk areas, including Hospitals and adjacent public areas. Specimens were morphologically identified and screened via microscopy. Molecular detection of E. bieneusi and E. intestinalis was performed using PCR targeting the 18sRNA region. DNA was extracted from pooled samples (10 cockroaches/pool) and amplified under standardized thermocycling conditions. All cockroaches were identified as Periplaneta americana (77.5 %) and Blattella germanica (22.5 %). In molecular assay, three positive case of E. bieneusi was detected, However, no E. intestinalis DNA was identified via PCR. This study reports the first molecular detection of E. bieneusi in Shiraz cockroaches. In continue, it records no evidence of E. intestinalis, which suggesting climatic or environmental barriers to limit this microsporidian persistence in this arid region. These findings highlight the need for integrated vector management and advanced molecular surveillance to elucidate the epidemiology of understudied pathogens like microsporidia in rapidly urbanizing regions.